Analyse des matières de la playlist vidéo de la grammaire française sur la chaîne YouTube de la Ccube Academy comme média alternatif pour l’apprentissage de la grammaire - Ana Maryana; Sri Handayani (Universitas Negeri Semarang, 2024)
Ccube Academy is a YouTube channel that studies French. This channel provides various videos needed to learn and understand French grammar, and the videos also provide many variations with animations that are not boring, and the language is simple, easy to understand, and available. Subtitles make learning French grammar easier. On the Ccube Academy YouTube channel, there are 12 video playlists, namely French conversation, DELF A1 B1 B2, Ccube Academy, CcubeAcademy.com, French grammar, Learn French, DELF B1, Animated short films, French lessons, Delf A1 junior oral comprehension, Preparation for the DELFI A1 exam, Learn the French language, and there are 229 videos with 270,000 subscribers. The playlist used to learn grammar is a French grammar playlist containing nine grammar-related videos, and these videos can be an alternative media that makes learning French grammar easier.